Sosialisasi Penulisan Jurnal Untuk Memotivasi Belajar Dalam Upaya Meningkatkan Kesiapan Belajar Dan Keterampilan Menulis Mahasiswa - Abdullah, Rachmad; Setyorini, Nanis; Faisal, Mohammad (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2024)
Teachers as mentors and facilitators of students have limited teaching hours so they cannot act as widely as possible, especially in teaching writing skills. On the other hand, students or college graduates must have good writing skills. However, most students feel less motivated to be ready to learn independently in order to improve their writing skills. The lack of student learning motivation to improve these skills is the focus of the problem in this community service agenda. This community service aims to increase student learning motivation through the socialization of journal writing to improve students' learning readiness and writing skills. The objects used were STIESIA Surabaya Semester 6 Class SMX students because most students still did not understand the concept of journal writing. The socialization event was carried out in two sessions, formally and informally, with the aim of arousing learning motivation according to students' desires and learning patterns. Session 1 was carried out formally with material provided around journal writing. Meanwhile, Session 2 was carried out informally using the one-on-one consultation method so that students could better understand their shortcomings in writing journals. The results obtained based on the guidance sheets and journal drafts collected by students showed that the socialization of journal writing could increase students' learning motivation to be more ready to learn and more skilled in writing